Unpacking the Role of Mobile Applications in EFL Learners’ Vocabulary Acquisition: A Phenomenological Study - Harahap, Sartika; Hidayani, Syarifah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
This study explores elementary school students’ experiences and perceptions of using Mobile-Assisted Language Learning (MALL) through the Quizlet application in learning English vocabulary as a foreign language. A qualitative research design with a phenomenological approach was employed to gain an in-depth understanding of how students experience and interpret the use of mobile applications in vocabulary learning. The participants consisted of 25 fourth-grade students from an elementary school in Mandailing Natal, Indonesia. Data were collected through classroom observations, semi-structured interviews with students, teachers, and parents, as well as documentation analysis of students’ activities on the Quizlet application. By focusing on elementary EFL learners in a rural Indonesian context, this study provides a contextualized perspective on MALL implementation at the primary education level, which has received limited attention in previous research. The phenomenological approach highlights how pedagogical practices and sociocultural conditions mediate young learners’ engagement with mobile technology. The findings reveal that the use of Quizlet offered positive learning experiences for elementary students. Interactive features such as digital flashcards, matching games, and immediate feedback enhanced students’ motivation and engagement in learning English vocabulary. Repeated exposure supported by visual and audio elements helped learners understand and retain n tp ew words more effectively. However, students continued to experience difficulties in productive aspects of vocabulary, particularly spelling and pronunciation, and encountered challenges related to limited internet access and shared device use. The study suggests that Quizlet can support vocabulary learning for primary EFL learners when it is pedagogically integrated with teacher guidance and adequate learning support.